EL-ESÂLIBU'L-BELAĞIYYE FI'L-HIVARI'L-KUR'ÂNIYYI –SÛRETU'L-A'RAF NEMUZECEN- - MULLA, ZANA ASAAD (Fırat Üniveristesi, 2019)
Bu çalışmada Araf suresi özelinde Kur'ân-ı Kerim'deki diyalogların sanatsal ve estetik güzelikleri üzerinden durulmuştur. Bu da bu diyaloglardaki belagat sanatlarına ve belagat üsluplarındaki çeşitliliğe değinme yoluyla gerçekleştirilmiştir. Ayrıca diyalog unsurlarının şekilleri, önemli nitelikleri ve onu diğer hitap tarzlarından ayıran özellikleri ortaya konmuştur. Bu diyaloglarda haber, inşâ, kasr, îcâz, itnâb ve müsâvât gibi meânî üslupları, teşbih ve mecaz gibi beyan üslupları, cinas ve tıbak gibi bedi' üslupşarı yer almıştır. Bu çalışmanın en önemli hedeflerinden biri Kur'ân diyaloglarında bulunan belagat sırlarını ve sanatsal özellikleri ortaya koymaktır. Anahtar Kelimeler: Kur'ân, Arapça, Üslup, Diyalog, Belagat

This study is an attempt to reflect the literary value of the dialogue and its techniques and aesthetics in the Holy Quran in Surat al-A'raf specifically, by addressing the eloquence of this dialogue and the diversity of its rhetorical methods after manifesting its formalities; the most important characteristics and features that distinguish it from other speeches; methods of semantics in dialogue includes: statements and composition, exception, brevity, redundancy and equality. As for methods of statement, it includes analogies and metaphor. Also, methods of language enhancement include anagrams and antithesis. The most important objectives of the thesis: highlighting the artistic and hidden rhetorical aspects which are included in the dialogue of the Holy Quran. Keywords: Quran, Arabic, methods, dialogue, rhetoric
A'raf suresi örneğinde Kuran diyaloglarında belağat üslupları (The rhetorical methods in the Quranic dialogue - Surat Al - A'raf model)
Keywords: Din; Dilbilim; Doğu Dilleri ve Edebiyatı